The Effect of Aluminum Source on Performance of Beta-Zeolite as a Support for Hydrocracking Catalyst - Mina Hadi; Hamid Reza Aghabozorg; Hamid Reza Bozorgzadeh; Mohammad Reza Ghasemi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
In this paper, three different kinds of aluminum sources (sodium aluminate, aluminum sulfate and aluminum isopropylate) were used for preparing of nano beta-zeolite. The as synthesized zeolites were mixed with the as prepared amorphous silica-alumina to produce the supports for hydrocracking catalyst. The prepared supports were used for preparation of NiMo/silica alumina-nano beta-zeolite by impregnation method. The influence of the aluminum source for preparation of beta-zeolite on the performance of the prepared catalysts has been studied. The samples were thoroughly characterized by X-Ray diffraction method (XRD), field emission-scanning electron microscopy (FE-SEM), N2 adsorption-desorption isotherms (BET), temperature programmed desorption (TPD) and temperature programmed reduction (TPR) methods. The catalysts performance was evaluated by vacuum gas oil (VGO) hydrocracking at 390 oC in a fixed bed reactor. The XRD patterns showed that the beta-zeolite samples obtained from the present methods were pure and highly crystalline and the crystal size of the prepared zeolites were in nanometer scale. Crystallite size of nano beta-zeolite synthesized by aluminum isopropylate [Al(iPrO)3] was smaller than those of prepared by the other aluminum sources. The catalyst containing this zeolite with higher surface area (231 m2/g) and more available acid sites (1.66 mmol NH3/g) possessed higher activity and selectivity to gas oil (71.9 %).